Comprehensive Transcriptome and Proteome Analyses Reveal the Modulation of Aflatoxin Production by Aspergillus flavus on Different Crop Substrates - Li, Xu; Jiang, Yiran; Ma, Longxue; Ma, Xiaoyun; Liu, Yang; Shan, Jihao; Ma, Kang; Xing, Fuguo (Frontiers in Microbiology, 2020)
As a natural severe contaminant of stored grains and other crops worldwide, Aspergillus flavus can produce aflatoxins (AFs), the most powerful naturally producing toxic and hepatocarcinogenic compounds. AFs production is regulated by diverse factors including AFs cluster genes, transcription factors, regulators and environmental factors. Among them, crop substrate is one of the most important factors. Here, we found that AFB1 production was significantly higher in maize and rice broth than in peanut broth. To clarify the mechanisms involved, complementary transcriptomic and proteomic analyses were performed to identify changes in A. flavus incubated in the three crop substrates. The results indicated that fewer genes and proteins were differentially expressed between maize and rice substrates, whereas more differentially expressed genes were observed between maize/rice broth and peanut broth. In particular, the genes involved in the initial step of AFs biosynthesis (aflA, aflB, and aflC) and the ACCase-encoding gene accA were significantly up-regulated on the maize and rice substrates. KEGG and GO enrichment analyses indicated that carbon-metabolism-related genes were obviously enriched in the maize broth, and the genes involved in acetyl-CoA accumulation and consumption were up-regulated and down-regulated, respectively. Several genes involved in the regulation of AFs biosynthesis including veA, ppoB, snf1, and the GPCR genes, were differentially expressed on the three substrates, suggesting that these genes may be also involved in sugar signal sensing, transfer and regulation. Interestingly, by the correlation analyses of transcriptome and proteome, trehalose metabolism genes, aldehyde dehydrogenase gene, and tryptophan synthase gene were found to be relevant with the regulation of AFs production on different crop substrates. Taken together, the differential expressions of the AFs cluster genes, several regulatory genes and carbon metabolism genes were involved in the comprehensive modulation of AFs production on different crop substrates.